Clinical Reasoning: A 59-Year-Old Man With Thymoma and Constitutional Symptoms, Seizures, and Multifocal CNS Lesions. (13th December 2022) - Stopschinski, Barbara E.; Fredrich, Sarah; Vernino, Steven; Phillips, Lauren; Blackburn, Kyle M.
Abstract : A 59-year-old man first presented for an episode of left arm numbness. During workup, a thymoma was incidentally discovered and resected. The symptoms in his left arm were attributed to a cardiac pathology. One month later, he began to experience fatigue, weight loss, and anorexia, followed by one generalized tonic-clonic seizure. Workup including toxic and metabolic screening and MRI of the brain were unremarkable. He was started on an antiseizure medication and did well for 2 years, when his symptoms recurred. Repeat MRI of the brain showed multiple cortical T2-weighted fluid-attenuated inversion recovery (T2/FLAIR) hyperintense lesions without enhancement or diffusion restriction. Further workup included spinal MRI, CT of the chest/abdomen/pelvis, CSF studies, and autoimmune/paraneoplastic panels in CSF and serum, all of which were unremarkable. Serum testing was positive for striational antibodies, acetylcholine receptor (AChR)–binding antibodies, and AChR-modulating antibodies. He received high-dose steroids and plasma exchange with resolution of his symptoms and has since been stable on mycophenolate mofetil. This presentation highlights the rare association between thymoma and encephalitis. Prompt identification and treatment is critical. This article discusses the diagnostic approach to this rare presentation including essential features of the clinical presentation, appropriate workup, pertinent differential diagnoses, and key points for the treatment of these patients.